A New Calibration Method of Stereo Line-Scan Cameras for 2D Coordinate Measurement - Wang, Guohui; Zhao, Linjie; Zheng, Hao (Frontiers in Physics, 2022)
Camera calibration plays an important role in various applications including machine vision and optical measurement. In this paper, we propose a new calibration method of stereo line-scan cameras for 2D coordinate measurement using a simple calibration target rather than requiring complex calibration patterns or an auxiliary area-scan camera. Considering the viewing planes associated with the stereo line-scan cameras are coplanar, an imaging model combining perspective projection and lens distortion are established and can depict the relationship between the 2D world coordinate and its corresponding 1D pixel coordinates of the image pairs. A two-step calibration algorithm is proposed to obtain the optimal values of intrinsic, extrinsic and distortion parameters of stereo line-scan cameras. The performance of the proposed camera calibration method is evaluated on 2D coordinate measurement and the experimental results demonstrate that the proposed method is more effective and accurate than the existing method.